The methodological challenge of cross-national qualitative research: Comparative case study interviews in Australia and Japan - Martinus, K.; Hedgcock, Dave (2015)
© Emerald Group Publishing Limited. Purpose – The purpose of this paper is to highlight the difficulties faced during the interview process in a cross-national qualitative comparative case study between Japan and Australia. It discusses the challenges in producing insightful data and preserving the integrity of findings when methodologies are influenced by different cultural and professional environments. Design/methodology/approach – The paper explores literature on cross-national qualitative research in the context of policy research as well as the philosophical and professional differences between Japan and Western countries (like Australia). It reflects on practical examples and strategies used by the researcher during the ethics and interview processes when adapting widely accepted qualitative case study methodology to suit the Japanese cultural and professional environment. Findings – The paper finds that linguistic, cultural, professional and philosophical differences between the countries challenged initial researcher assumptions that comparability between the case study regions would be maintained through the application of accepted methodologies and an “insider” status. It observes that the quest to generate rich and insightful data places the character and capability of the researcher as central in the research process. Originality/value – This paper provides practical examples and strategies for social science researchers using interview methods in Japan and Australian. It points to a need for further research on the ambiguous and elusive nature of the “insider” paradigm as well as the “comparability” of cross-national qualitative case studies when methodological “flexibility” is used to enrich and preserve the integrity of research findings.